2013
DOI: 10.26786/1920-7603(2014)8
|View full text |Cite
|
Sign up to set email alerts
|

Pollination deficits in UK apple orchards

Abstract: Apple production in the UK is worth over £100 million per annum and this production is heavily dependent on insect pollination. Despite its importance, it is not clear which insect pollinators carry out the majority of this pollination. Furthermore, it is unknown whether current UK apple production, in terms of both yield and quality, suffers pollination deficits and whether production value could be increased through effective management of pollination services. The present study set out to address some of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 28 publications
2
20
4
Order By: Relevance
“…Furthermore, our results confirmed the high economic value of insect pollination in apple production, as seen in previous studies (Garratt, Breeze, et al., 2014; Garratt, Truslove, et al., 2014; Geslin et al., 2017) and show a potential gross return attached to floral planting of about R4 160 per ha ( c . $220).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, our results confirmed the high economic value of insect pollination in apple production, as seen in previous studies (Garratt, Breeze, et al., 2014; Garratt, Truslove, et al., 2014; Geslin et al., 2017) and show a potential gross return attached to floral planting of about R4 160 per ha ( c . $220).…”
Section: Discussionsupporting
confidence: 91%
“…However, in contrast with observations in other temperate regions (e.g. Garratt, Breeze, et al., 2014; Garratt, Truslove, et al., 2014), most visits to apple flowers were carried out by the endemic honey bee A . mellifera capensis .…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…There is consensus that wild pollinators can contribute in different ways to improve pollination efficiency in crops (e.g., higher visitation rate, increase in pollen transfer, among others), and interfere with the behavior of foraging by honeybees, improving total pollination performance [24][25][26]. Moreover, it has been observed that an increase in pollinators' diversity can favor fruit quantity and the quality of the harvests, favoring the final production and, therefore, the economic return for the producer (e.g., [27,28]).…”
Section: Native Pollinatorsmentioning
confidence: 99%
“…Solitary bees may therefore be particularly vulnerable to the effects of exploitative competition, particularly when resources are scarce. However, this is not well understood (see , despite the importance of these bees for the pollination of many crop and wild plants (Williams and Kremen 2007;Garratt et al 2014;Garibaldi et al 2014;Mallinger and Gratton 2015).…”
Section: Introductionmentioning
confidence: 99%